The Effect of Kajauma Pudding (Green Bean Date Pudding) on Breast Milk Production for Postpartum Mothers - Suherlin, Ika; Astuti, Siti Choirul Dwi; Yulianingsih, Endah (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
Breastfeeding mothers are one of the groups that are included in the nutritionally vulnerable group because breast milk is the main source that babies get from the mother. Therefore, mothers who are breastfeeding must pay attention to the nutritional intake they consume. Breast milk production is greatly influenced by the food the mother eats, even though a mother's regular and nutritious diet is very necessary to influence breast milk production, because the breastfeeding glands cannot work perfectly without sufficient food. To produce good breast milk production, the mother's diet must contain sufficient calories, protein, fat and vitamins and minerals. This research aims to determine the effect of kajauma (date nut) pudding on the production of postpartum women in Bone Bolango district. The type of research used was pre-testing with a pretest posttest control group design for 30 respondents. In this design there are two groups selected at random, one group is given green bean pudding and the second group is given kajauma (green date bean) pudding. From the difference in average breast milk production before and after the treatment, the biggest change in breast milk production was in the treatment group with kajauma pudding. The Independent T-Test obtained p=0.006 (<0.05), and the paired T Test carried out on changes in the two groups obtained p=0.000 (<0.05), so it can be concluded that the 2 treatment groups with kajauma pudding had an effect. which is better for breast milk production than treatment with green bean pudding.